Developing Linguocultural Competence in Foreign Language Education: a Pilot Study Among First-year Kazakh Department Students at Al-Farabi Kazakh National University - Dyussembekova, Z.A.; Sansyzbayeva, S.K. (Karagandy University of the name of academician E.A. Buketov, 2025)
This article addresses the pertinent issue of developing linguocultural competence among first-year students of the Kazakh Department at a language-focused university within the context of a foreign language education setting. The relevance of this research is driven by the growing need to cultivate not only language skills but also communicative readiness for effective intercultural communication among future specialists in today's globalized world. The study aimed to comprehensively investigate the impact of integrating a systematic cultural component into the foreign language curriculum on the dynamics of linguocultural competence development and the process of linguistic personality formation in students. To achieve this objective, the authors developed and implemented a multifaceted mixed-methods approach, encompassing textual analysis of authentic materials, quantitative questionnaires administered to students at the initial and final stages of instruction, a series of pedagogical experiments employing interactive technologies and multimedia resources, and practice-oriented project-based learning. The empirical foundation of the study is based on data collected from 23 first-year students of the Kazakh Department at Al-Farabi Kazakh National University. The findings of the study revealed that the purposeful and systematic inclusion of cultural context in foreign language education exerts a substantial positive influence on all components of students’ linguocultural competence, significantly enhancing their linguistic, cultural, and communicative proficiency. In particular, it was experimentally demonstrated that the regular use of bilingual texts, interactive work formats and multimedia resources, as well as purposefully designed specialized educational modules focused on the culture of the target language, particularly effectively stimulate the understanding and tolerant acceptance of cultural differences, and also contribute to the active development of intercultural communication skills. The obtained research results convincingly confirm the strategic necessity of consistent integration of the linguocultural component into modern foreign language education programs and offer specific practical recommendations for the further improvement of foreign language teaching methodologies in multicultural environments.
Шет тілін оқытудағы лингвомәдени құзыреттілікті дамыту: әл-Фараби атындағы Қазақ ұлттық университеті қазақ бөлімінің бірінші курс студенттері арасында пилоттық зерттеу
Развитие лингвокультурной компетенции в процессе обучения иностранному языку: пилотное исследование среди студентов первого курса казахского отделения Казахского национального университета имени Аль-Фараби
Keywords: Linguocultural Competence; Intercultural Communication; Foreign Language Education; Cultural Integration